Techno-Economic Assessment of Peruvian Stipa Ichu Microfibres by Steam Explosion - Ramos Nazario, Victor (2023)
Steam explosion as a pre-treatment for lignocellulosic fibers is an eco-friendly technology for obtaining cellulose microfibres. This study used a sustainable process design to produce Stipa Ichu (endemic fiber) cellulose microfibres on a pilot scale. Pseudolignin models and experimental data from recent studies were used to validate and simulate the steam explosion in a range of 150 to 220°C using acetic acid concentrations of 0.1 to 0.3 g/g of fiber. A peak yield of 92% was obtained for lignin recovery. The proposed process, which would produce 5 tons of dried cellulose microfibres per year, is economically feasible with an ROI of 48% and a PBP of 2.45 years. Additionally, the process is environmentally viable, with an E-factor of 9.42.